Use-case and sequence diagram models for developing transient stability software. - Suyono, Hadi; Nor, Khaled Mohamed; Yusof, S.; Rashid, A. H. A. (2006)
Transient stability (TS) software is a tool that is used to analyze the stability of power system after subjected a large disturbance. The transient stability software tool can be built by any approaches such as procedural programming, object-oriented programming (OOP), or component-oriented programming (COP). The component-oriented based on the object-oriented design (OOD) is proposed for developing the TS software in this paper. In the component development, use cases and sequence diagram models are required to identify the sub-system and process involved in the TS problem. The use-cases are made according to the components and objects required in the TS tool such as load flow solver, transient stability solver, linear solver, and object-oriented power system model (OO-PSM). A sequence diagram model represents the detailed process of a use case. Both use-case and sequence diagram models required for TS software tool are focused in this paper. The unified modeling language (UML) which is a standard object modeling for developing component- and object- oriented design is used to develop the use cases and sequence diagram models.